Epidemiology of rabies cases among international travellers, 2013–2019: A retrospective analysis of published reports. Issue 36 (July 2020) - Gautret, Philippe; Diaz-Menendez, Marta; Goorhuis, Abraham; Wallace, Ryan M.; Msimang, Veerle; Blanton, Jesse; Dacheux, Laurent; Parize, Perrine; Blumberg, Lucille; Bourhy, Hervé; Grobusch, Martin P.
Abstract: Background: Sixty cases of rabies in international travellers from 1990 to 2012 were previously reviewed. We present here an update of rabies cases in international travellers from 2013 to 2019. Methods: We systematically reviewed the existing literature and collected 23 cases of rabies in individuals who crossed an international border between the time of infection and diagnosis, or who were infected following expatriation or migration. Results: Most cases were in male adult travellers and diagnosed in Europe and the Middle East, with most exposures in Asia or in Africa. Migrants originating from rabies-endemic low-and-middle income countries and their descendants accounted for two thirds of cases. Other cases were in tourists, business travellers and expatriates. Median travel duration (excluding migration trip) was 60 days (range 7–240 days). Most cases were due to dog bites and most common clinical presentation was furious rabies. In most patients (74%), no rabies post-exposure prophylaxis (RPEP) was administered before rabies symptoms appeared. Other patients received incomplete RPEP series. Conclusion: Rabies should be suspected in any patient with encephalitis or paralysis who travelled to, or migrated from a rabies-endemic country. Comprehensive information about a rabies risk should be given to travellers to rabies endemic countries, notably migrants visiting friends and relatives.